A7 THE ROLE OF PROTEASE-ACTIVATED RECEPTOR-2 IN GIARDIA INDUCED DISRUPTIONS OF THE INTESTINAL MUCUS LAYER. (1st March 2018) - Fekete, E; Amat, C B; Allain, T; Saiffeddine, M; Hollenberg, M; Chadee, K; Buret, A
Abstract: Background: Disruptions of the intestinal mucus barrier have been implicated in a variety of intestinal disorders. The mechanisms behind these disruptions remain unclear. We recently demonstrated that the enteric parasitic pathogen Giardia duodenalis alters the mucus layers of the small and large intestines at least in part via Giardia cysteine proteases. Aims: We hypothesized that goblet cell function and mucus disruptions are modulated by activation of protease activated receptor 2 (PAR2), which is highly expressed through the gastrointestinal tract, and is known to regulate mucus production in the airway and stomach. We aimed to determine whether Giardia's cysteine proteases cleave and activate PAR2 on intestinal goblet cells, leading to modulation of their mucus producing activity. Methods: The human colonic epithelial cell line LS174T was used for in vitro mucus studies. The presence of functional PAR1 or PAR2 was assessed with calcium signaling assays using the specific activating peptides TFLLRN or 2fLIGRLO, respectively. MUC2 mucin gene expression was assessed through quantitative PCR (qPCR) in LS174T incubated with either Giardia trophozoites or activating peptides, and with pre-treatment of cells with the PAR2 antagonist p2Pal-218S pepducin. qPCR was also used to measure changes in PAR2 gene expression in response to Giardia . Wild type and PAR2 deficient mice were infected with Giardia trophozoites. The thickness of the mucus layer was measured by fluorescently staining mucus with fluorescein-coupled WGA, and expression of Muc2 and Muc5ac genes were determined using qPCR. Results: LS174T express functional and responsive PAR2, but little or no PAR1. Treatment of cells with 2fLIGRLO (PAR2 agonist), but not TFLLRN (PAR1 agonist), increased MUC2 gene expression. Incubation of cells with Giardia trophozoites also increased MUC2 mRNA production, and this increase was abolished by pre-treatment of cells with a PAR2 antagonist. Giardia decreased PAR2 mRNA in LS174T. Giardia infection increased the expression of Muc2 and Muc5ac in the colon, and increased Muc5ac expression in the jejunum of wild-type mice compared to uninfected controls. In PAR2-/- mice, Giardia infection reduced the expression of Muc5ac, but not Muc2 in the jejunum, but did not affect gene expression in the colon. Giardia infection caused a thinning of the mucus layer in wild-type mice. In contrast, the infection induced a thickening of the mucus layer in PAR2-/- mice. Conclusions: Using a model of Giardia infection, the findings demonstrate that PAR2 plays a significant role in mucin gene regulation and function in mice and in a human colonic goblet cell line. Funding Agencies: CCCNSERC